PERTIMBANGAN HAKIM PADA PUTUSAN DECLARATOIR TERHADAP HAK MILIK ATAS TANAH - Nofaomasi Laia (Jurnal Panah Hukum, 2026)
Land ownership rights are hereditary, strongest and most complete rights that will exist as long as the owner lives, and if he dies, it can be transferred to the heirs. Disputes over land ownership rights are often triggered by the increasing number of people but the condition of the land remains the same. One of the land disputes that has been examined and tried by the first-instance district court is decision number 4/Pdt.G/2024/PN.Bgl. In the decision, the panel of judges stated that the defendant had indeed committed an unlawful act, as regulated in Article 1365 of the Civil Code. The type of research used is normative legal research with a statutory regulatory approach method, a case approach, and an analytical approach. Data collection was carried out using secondary data obtained through library materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis used was a qualitative analysis that was descriptive in nature and conclusions were drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the judge's consideration in passing a verdict on the defendant is unfair, where the defendant has been proven guilty of committing an unlawful act, but the judge did not impose a penalty of compensation on the plaintiff as regulated in Article 1365 of the Civil Code. The author suggests to law enforcement in this case the panel of judges, that in deciding a case that has been proven to have committed an unlawful act, they should consider the material and immaterial losses to the injured party.